GE_GERICHTE P/17038/2020 vom 2. März 2021 - GE Cour de justice (2021)
EXPULSION(DROIT PÉNAL);VIOLATION DE DOMICILE;VOL(DROIT PÉNAL);DOMMAGES À LA PROPRIÉTÉ(DROIT PÉNAL);TENTATIVE(DROIT PÉNAL);ENTRÉE ILLÉGALE;SÉJOUR ILLÉGAL | CP.66a; CP.186; CP.139; CP.144